The Aeration Process on the Reduction of COD, BOD, and TSS Parameters in Palm Oil Mill Liquid Waste through Aerobic Treatment - Suryadi, Jefri; Muhelni, Leila; Edinov, Sanny; Mukhtar, Dertha; Anwar, Hendra (The Future of Education Journal, 2025)
Palm oil mill liquid waste contains high organic matter and nutrients, such as Chemical Oxygen Demand (COD), Biological Oxygen Demand (BOD), Total Suspended Solid (TSS), and low acidity (pH). If this liquid waste is discharged directly into water bodies without treatment, it will pollute the environment and disrupt aquatic ecosystems (National Standardization Agency.2016). One of the efforts to treat liquid waste in palm oil mills can be done by aeration process. The aeration process aims to increase the level of dissolved oxygen (DO) in liquid waste so that aerobic microorganisms can effectively degrade organic matter. The aeration process can be carried out by several methods, such as using an aerator (Fitri, A., Susanto, H., & Budiaman, I. G. S. 2017).)Dissolved Oxygen (DO) Increased from 0 hours to 3.9 Mg/l, 24 hours to 5.7 Mg/l and 72 hours to 6.3 Mg/l. PH Increased from 0 hours to 4.32, 24 hours to 4.78 and 72 hours to 5.32 So the increase in DO and PH during the Aeration process is very helpful in reducing the level of pollutants in palm oil mill waste The effectiveness of the aerobic aeration process in the treatment of palm oil mill waste is able to reduce the level of TSS, COD, BOD, for TSS at 0 hours 461 m/L, 24 hours 403 m/L ,72 hours 275 m./L for COD at 0 hours 4240 m/L 24 hours 3816 m/L ,72 hours 1018 m/L for BOD at 0 hours 506 m/L, 24 hours 358 m/L ,72 hours 298 m/L.